Design of a nationwide survey on palliative care for end-stage heart failure in Japan. Issue 2 (February 2018) - Kurozumi, Yuma; Oishi, Shogo; Sugano, Yasuo; Sakashita, Akihiro; Kotooka, Norihiko; Suzuki, Makoto; Higo, Taiki; Yumino, Dai; Takada, Yasuko; Maeda, Seiko; Yamabe, Saori; Washida, Koichi; et al.
Highlights: Palliative care for end-stage heart failure has yet not been established. We conducted the nationwide survey of palliative care for heart failure. This survey collected information to improve the quality of palliative care. Abstract: Background: The term palliative care has historically been associated with support for individuals with advanced incurable cancer, so cardiologists and cardiac nurses may be unfamiliar with its principles and practice. However, palliative care is now a part of end-stage heart failure management. We conducted the first nationwide survey to investigate the status of palliative care for heart failure in Japan. Methods and results: A self-reported questionnaire was mailed to all Japanese Circulation Society – authorized cardiology training hospitals ( n = 1004) in August 2016. The response deadline was December 2016. The survey focused on the following topics: basic information about the facility and multidisciplinary team, patient symptoms for palliative care, positive outcomes after providing palliative care, drug therapy as palliative care for patients with heart failure, advance care planning with patients and their families, and impediments to providing palliative care to patients with heart failure. The results of the survey will be reported in detail elsewhere. Conclusions: Current guidelines on palliative care do not specifically address what team members should be involved, what drugs should be used, or when palliative care should be started. This survey collected information to improve the quality of palliative care and provide more specialized palliative care within the limits of resources.